ChemInform Abstract: Flow Synthesis of Arylboronic Esters Bearing Electrophilic Functional Groups and Space Integration with Suzuki—Miyaura Coupling without Intentionally Added Base. Issue 12 (14th March 2013) - Nagaki, Aiichiro; Moriwaki, Yuya; Yoshida, Jun‐ichi
Abstract The synthesis of boronic esters (III) proceeds readily in a flow microreactor by a halogen‐lithium exchange reaction of aryl halides and a subsequent borylation of aryllithium intermediates (12 examples).